"Study of Endoparasites of Rodents and their Zoonotic Importance In Ahvaz, South West Iran" - EB Kia; MM Homayouni; A Farahnak; M Mohebali; S Shojai (Tehran University of Medical Sciences, 2001)
During an investigation on the endoparasites of rodents in Ahvaz, Khuzestan province, south west Iran, a total of 90 rodents including 14 Mus musculus,4 Rattus rattus and 72 R. norvegicus were trapped from different localities of Ahvaz and its suburbs, during 1998- 2000, using live traps. Examination of different tissues, identification of parasite species and serological tests were carried out in School of Public Health and Institute of Public Health Research. Results showed that the variation among helminth species was wide especially those which arthropods are involve in their life cycles. The most prevalent species of rodents was R. norvegicus in which Trypanosoma lewisi and Trichosomoides crassicauda were the most prevalent species of protozoan and helminth parasites, respectively. Gongylonema monigi, Streptopharagus kuntzi and Rictularia ratti from R.norvegicus and G. neoplasticum from both R.norvegicus and R. rattus are reported for the first time in Iran. Report of Physocephalus sexalatus from R.norvegicus apparently comprises an new host species in the world. The public health importance of zoonotic species are discussed.